Analysis Of Leading Sectors In West Sumatra Province - Hashfi, Hasbiul (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
This study analyzes the changing economic structure of West Sumatra, Indonesia from 2017-2022 using location quotient (LQ) and dynamic location quotient (DLQ) techniques. The analysis identifies current concentrated export-oriented sectors like agriculture, manufacturing, transportation and government services based on high LQ values. Meanwhile, DLQ analysis reveals emerging competitive sectors such as mining and declining sectors like agriculture based on shifts in employment. The combined LQ and DLQ analyses provide insights into West Sumatra’s economic base and structural changes. Electricity, gas, transportation, finance and government administration appear strong and growing in competitiveness based on high LQ and high DLQ values. Further investigation through surveys, focus groups and value chain analysis is recommended to translate these findings into tailored strategic policies to leverage West Sumatra’s regional competitive advantages. This initial screening provides insights into West Sumatra’s changing economic geography.